Dielectric anisotropy, memory state and diffraction efficiency properties of the spiropyranylazobenzoate AP-SPAB7 doped nematic liquid crystal - Yakuphanoğlu, Fahrettin; Okutan, Mustafa; Koeysal, Oguz; Keum, Sam-Rok (Elsevier Sci Ltd, 2008)
Dielectric anisotropy, memory state and diffraction efficiency properties of E7 liquid crystal and AP-SPAB7 doped liquid crystal composite are investigated by dielectric and electrical conductivity properties. The liquid crystals exhibit dielectrically controlled positive dielectric anisotropy (p-type Delta epsilon) with the critical frequency transition to negative dielectric anisotropy (n-type Delta epsilon) behavior. The AP-SPAB7 doping does not change the memory state properties of LC, while the doping changes dependency of dielectric anisotropy on applied voltage. The diffraction efficiency is significantly enhanced in the AP-SPAB7 doped LC. The refractive index modulation values of the E7 and E7/AP-SPAB7 were found to be Delta n = 3.9 x 10(-3) and An = 9.7 x 10(-3), respectively. The AP-SPAB7 doping increases the refractive index modulation of E7 LC. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: liquid crystal; AP-SPAB7; dielectric anisotropy; memory state